Sensory marketing and consumer profile: : the psychology of color in product design - Moral Jiménez, María de la Villa; González Carreño, Celia (Pensando Psicología, 2023)
Background: There are multiple factors that influence the consumer during the purchase process and it has been confirmed that visual signals mediate a large part of their decisions, color being one of the visual elements with the most persuasive power. The objective of this study has been to assess the influence of color as a resource used in the strategies designed from the field of sensory marketing, as well as the construction of two types of consumer profiles in order to direct these strategies more specifically. Methodology: There was a sample of 452 participants with an age range between 18 and 74 years (X = 42.98; DT = 15.351) who answered about their consumption habits and behaviors, as well as about the perception of influence of color in the purchasing process. Results: The value of color as a transmitter of information has been confirmed, in addition to its potential implication in establishing a good emotional connection between consumer-product-brand. Those consumers with a more emotional profile are more influenced by the use of color in marketing strategies than those with a more rational profile. Likewise, the positive evaluation of the products in which there is congruence between the color of the package and the expected flavor, smell or category of the product has been verified, as well as the perception of more innovative in those in which there was incongruity between the products. Conclusions: The importance of product color in consumer decision-making is valued, hence its value as a resource from sensory marketing is influenced.
Keywords: purchase decision; product design; sensory marketing; consumer profile; psychology of color